Pengaruh Pengetahuan Kewirausahaan Dan Literasi Digital Terhadap Perilaku Berwirausaha Melalui Variabel Efikasi Diri Kewirausahaan Sebagai Mediasi Pada Siswa Kelas XI IPS di SMAN 20 Surabaya - Meyra Yuniar, Audyna; Tjipto Subroto, Waspodo (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
The aim of this research was to analyze the influence of entrepreneurial knowledge and digital literacy on entrepreneurial behavior through the self-efficacy variable as a mediating variable in class XI IPS students at SMAN 20 Surabaya. The subjects of this research were 106 students who were taken as samples using the simple random sampling method. Data was collected using questionnaires and documentation. The data analysis technique uses Structural Equation Modeling (SEM) using SmartPLS 3 software. The results of this study show the effect of knowledge on entrepreneurial behavior, entrepreneurial knowledge has an effect on self-efficacy, digital literacy has no effect on entrepreneurial behavior, digital literacy has an effect on self-efficacy, and knowledge entrepreneurship influences entrepreneurial behavior through entrepreneurial efficacy, and the influence of digital literacy on entrepreneurial behavior through self-efficacy through mediation.